2013
DOI: 10.1007/s11255-012-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of N-acetylcysteine in preventing contrast-induced nephropathy in patients undergoing contrast-enhanced computed tomography: a meta-analysis of randomized controlled trials

Abstract: This review provides evidence of the efficacy of NAC in preventing the incidence of CIN and recommends that NAC be more widely used in high-risk patients undergoing contrast-enhanced CT. On the basis of the evidence reviewed, further research involving large RCTs may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
2
33
0
1
Order By: Relevance
“…Here, we demonstrated that GRP78 silencing led to the decrease in GSC properties and rendered them more sensitive to irradiation treatment, indicating GRP78's role in contributing to GSC stemness. This notion is supported by a previous study where GRP78 up-regulation was correlated to irradiation resistance in breast cancer cells [35]. Here, our data indicated that GRP78 up-regulation was accompanied by the increased level of c-Myc and β-catenin expression and led to increased resistance towards irradiation.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we demonstrated that GRP78 silencing led to the decrease in GSC properties and rendered them more sensitive to irradiation treatment, indicating GRP78's role in contributing to GSC stemness. This notion is supported by a previous study where GRP78 up-regulation was correlated to irradiation resistance in breast cancer cells [35]. Here, our data indicated that GRP78 up-regulation was accompanied by the increased level of c-Myc and β-catenin expression and led to increased resistance towards irradiation.…”
Section: Discussionsupporting
confidence: 89%
“…They determined no difference between these protocols. However, one meta-analysis published in 2013 and evaluating NAC therapy in preventing CIN explicitly stated that NAC was more effective 23 Our study compared the effectiveness of all three prophylactic options in the context of more specific radiologic imaging in a more specific patient group. Although all patients used at least one prophylactic option in the form of a precontrast bolus and infusion for at least 6 hours after contrast, the high level of development of CIN development, proceeding to severe renal insufficiency and hemodialysis requirements in some of these cases, is a finding requiring close attention from emergency physicians experiencing indecision between the risk of development of CIN and diagnosing or excluding PE.…”
Section: Discussionmentioning
confidence: 98%
“…Acetylcysteine has not been shown to prevent AKI associated with cardiac surgery or in patients with sepsis [77, 78]. In the setting of CI-AKI, results have been contradictory, but several meta-analyses suggest that acetylcysteine provides some protection against CI-AKI, especially in patients at high risk [76, 79, 80]. Due to the heterogeneity of study results, it is difficult to establish a clear consensus, but the KDIGO work group has proposed that oral acetylcysteine along with intravenous isotonic crystalloid solutions should be used in patients at high risk of CI-AKI [68].…”
Section: Treatment and Management Of Akimentioning
confidence: 99%